Tocqueville's political economy - Swedberg, Richard (Princeton : Princeton University Press, 2009)
"In Tocqueville's Political Economy, Richard Swedburg shows that Alexis de Tocqueville had a highly original and suggestive approach to economics - one that still has much to teach us today." "Through careful readings of Tocqueville's two major books and many of his other writings, Swedburg lays bare Tocqueville's ingenious way of thinking about major economic phenomena. When examined together, Swedburg argues, these books and other writings constitute an interesting alternative model of economic thinking, as well as a major contribution to political economy that deserves a place in contemporary discussions about the social effects of economics"--Jacket
The economy of the New World -- The other democratic economy -- Tocqueville's background in economics -- Tocqueville's approach to economic analysis -- Pauperism and the habits of property -- Politics in a democratic economy -- Foreign affairs and economic affairs -- Threats to the democratic economy -- Sorrento and the return to thinking -- The economy of the Old World -- Epilogue: Thinking with Tocqueville.
Includes bibliographical references (pages 285-336) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Tocqueville, Alexis de, -- 1805-1859.; Tocqueville, Alexis de, -- 1805-1859 -- Views on economics; Tocqueville, Alexis de, -- 1805-1859.; Tocqueville, Alexis de, -- 1805-1859.; Tocqueville, Alexis de, -- 1805-1859.; Tocqueville, Alexis de, -- 1805-1859.; Tocqueville, Alexis de, -- 1805-1859 -- Views on economics; Tocqueville, Alexis de, -- 1805-1859; Ancien régime et la Révolution (Tocqueville, Alexis de); De la démocratie en Amérique (Tocqueville, Alexis de); Economics -- Political aspects; Economics -- Sociological aspects; Économie politique et politique; BUSINESS & ECONOMICS -- Economics -- General; BUSINESS & ECONOMICS -- Reference; POLITICAL SCIENCE -- Public Policy -- Economic Policy; Economics; Economics -- Political aspects; Economics -- Sociological aspects; Economie